Knowledge, Attitudes and Actions of Farmers on Qanun Number 3 of 2016 About Controlling Productive Female Cattle and Buffalo in Aceh Besar District - Satria Nugraha; Teuku Reza Ferasyi; Nurliana Nurliana; Sugito Sugito; Teuku Zahrial Helmi (The International Journal of Tropical Veterinary and Biomedical Research, 2022)
The research was at determining the knowledge, attitudes, and actions of farmers on the Qanun number 3 of 2016 regarding the control of productive cows and buffaloes to avoid slaughtering productive cows and buffaloes so that livestock populations are maintained. This research was conducted using a survey method for three months starting from May 2021 to July 2021. Breeders were selected using the purposive sampling method and interviews were conducted by filling out a validated questionnaire. The data analysis method used was descriptive qualitative analysis using a structured questionnaire to 110 farmer respondents with the criteria of having 2 years of experience in raising cattle, and raising female cows. The livestock population has increased since Qanun Number 3 was issued in 2016. The results of this study indicate that the level of knowledge of farmers is in a good category (72.5%), attitude is a very good category (83.2%) and action is good category (72.5%).